The Idea of Emergence – an Overview - Maziarka, Tomasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
This article has an introductory character and systematizes the topic. It introduces the idea of emergence which is currently enjoying something of a renaissance and aims to bring order to the terminology associated with this idea. The article concerns the very beginning of the formation of emergentism and its intuitive understanding. It also presents the main concepts of representative authors of emergentism (S. Alexander, CL Morgan, Ch. D. Broad) as well as the numerous characteristics of emergence (synchronic and diachronic emergence, weak and strong emergence). The article concludes with a systematization of meanings and contexts in which the concept of emergence occurs.